2021
DOI: 10.1186/s12934-021-01622-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alternative integration sites in the chromosome and the native plasmids of the cyanobacterium Synechocystis sp. PCC 6803 in respect to expression efficiency and copy number

Abstract: Background Synechocystis sp. PCC 6803 provides a well-established reference point to cyanobacterial metabolic engineering as part of basic photosynthesis research, as well as in the development of next-generation biotechnological production systems. This study focused on expanding the current knowledge on genomic integration of expression constructs in Synechocystis, targeting a range of novel sites in the chromosome and in the native plasmids, together with established loci used in literature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 92 publications
3
24
0
Order By: Relevance
“…On day 18, the presence of the CT.353 TeBACD vector was confirmed in all carboys by PCR (see supplementary materials ), which demonstrated that the cultures retained the self-replicating vector for producing Te-PC in the absence of a selective pressure for the duration of the cultivation period. This is consistent with recent work that has demonstrated that self-replicating RSF1010-based plasmids appear stable in cultures without antibiotic selection for at least six weeks ( Nagy et al, 2021 ). Furthermore, the results suggested that the absence of kanamycin reduced cell stress and/or metabolic burden, which allowed for a small, but significant increase in Te-PC productivity.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…On day 18, the presence of the CT.353 TeBACD vector was confirmed in all carboys by PCR (see supplementary materials ), which demonstrated that the cultures retained the self-replicating vector for producing Te-PC in the absence of a selective pressure for the duration of the cultivation period. This is consistent with recent work that has demonstrated that self-replicating RSF1010-based plasmids appear stable in cultures without antibiotic selection for at least six weeks ( Nagy et al, 2021 ). Furthermore, the results suggested that the absence of kanamycin reduced cell stress and/or metabolic burden, which allowed for a small, but significant increase in Te-PC productivity.…”
Section: Resultssupporting
confidence: 93%
“…The yields of Te-PC in the Synechocystis mutant strains were comparable to that of native PC in wild-type Synechocystis , while the thermostability properties matched those from T. elongatus . Recent work has demonstrated that the level of eYFP expression from an RSF1010-based vector was 3-fold higher than eYFP expression from chromosomal integrations by natural transformation ( Nagy et al, 2021 ). Importantly, that study also showed that the self-replicating vector was retained for 42 days without antibiotic selection at lab scale, thereby suggesting that scale-up batch cultivation without antibiotic selection is feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, more biomass and ALA with lower CO 2 emission were observed by using PL instead of PLP in BY strains, since PLP may be an inhibitor to RuBisCo and Prk. 45 The biomass was significantly improved in RSSA-BY by 176% and CO 2 was reduced by 53.8%. In conclusion, this study achieved a robust strain A-RcYI with outstanding ALAS activity for efficient ALA production in E. coli.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…The results of Figure B and Table supplement that pRARE enhanced ALA production while CO 2 release was reduced, which may be attributed to the improvement on the cell behavior and protein quality with sufficient tRNA as aforementioned. Besides, more biomass and ALA with lower CO 2 emission were observed by using PL instead of PLP in BY strains, since PLP may be an inhibitor to RuBisCo and Prk . The biomass was significantly improved in RSSA-BY by 176% and CO 2 was reduced by 53.8%.…”
Section: Resultsmentioning
confidence: 99%
“…This method would likely be inefficient for the CRISPR/Cas9 vectors developed in this study, as RSF1010-replicon vectors are stably maintained in S6803 for prolonged periods under non-selective conditions. 46 Another option is to add a counter-selection marker to the vector, such as sacB from Bacillus subtilis that causes sucrose-sensitivity. 47 However, the sacB -method is only functional for glucose-tolerant wild type S6803 strains.…”
Section: Resultsmentioning
confidence: 99%